Кырӟамтэ кырӟан - Данилов Григорий Данилович (Удмуртия, 1991)
Экземпляры: ф-3 (ретроконверсия) / Инвентарный номер: 31471 / Цена: 2.70 / Сис.шифр: С(Удм) / Авт.знак: Д 18 / ГРНТИ: 17 / ББК: 84(2=411.2)6